Measurement of oil fraction in oil-water dispersed flow with swept-frequency ultrasound attenuation method - Yu, Han; Tan, Chao; Dong, Feng (International journal of multiphase flow, 2020)
•A swept-frequency ultrasound attenuation method based on droplet size estimation is proposed to measure oil fraction.•An ultrasonic attenuation model considering the absorption and scattering attenuation is established.•A chirp-based detection method is developed to quickly measure the ultrasonic attenuation of multiple frequencies.•Trust region algorithm combined with Gaussian QPSO is proposed for inversion calculation of phase fraction. It is very meaningful to measure the oil fraction of oil-water dispersed flow in pipelines. Traditional single-frequency ultrasonic methods measure the oil fraction by treating the dispersed flow with an average droplet size, which ignores the influence of the droplet size distribution and limits the measurement accuracy. Therefore, a swept-frequency ultrasound attenuation method based on droplet size distribution is proposed for the measurement of oil fraction. According to the characteristics of similar physical parameters and large droplet size of oil-water two phases, the Bouguer-Lambert-Beer's Law and McClements model are combined to predict ultrasonic attenuation in the oil-water dispersed flow, considering the attenuation effects of absorption and scattering. Due to the time-varying characteristic of the oil-water two-phase flow state, the chirp-based detection method is proposed to quickly measure the ultrasonic attenuation of multiple frequencies. For the nonlinear problem of ultrasonic attenuation response, trust region algorithm combined with Gaussian quantum particle swarm optimization is proposed for inversion calculation of oil fraction. Finally, the effectiveness of the ultrasonic attenuation mechanism model and inversion algorithm is verified by simulation and numerical calculation, and the experiments are carried out in the test device for liquid-liquid two-phase flow. The experimental results show that the proposed method can measure the oil fraction of oil-water dispersed flow with an average error less than 1.67% and a maximum error less than 3.57%.